Eksplorasi Alassan Pemuda Memilih Pesantren Salafiyah Untuk Memenuhi Kebutuhan Pendidikan: Persfektif Fenomenalogis di Desa Padarincang - Agusti, Suryadi; Kudus, Wahid Abdul (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This research aims to explore the subjective experiences of youth in Padarincang Village in choosing Salafiyah Islamic boarding schools (pesantren salafiyah) as an educational pathway amid the currents of educational modernization. The study employs Alfred Schutz’s social phenomenology approach to examine subjective meanings, motives for action, and the lived experiences (lifeworld) of youth who consciously choose pesantren as a space for self-formation. Schutz argues that human decisions cannot be separated from the stock of knowledge, past experiences (because-motives), and the goals individuals aim to achieve in the future (in-order-to motives). The findings show that the youths’ decision to study in pesantren is influenced by the internalization of religious values since childhood, a religious community environment, and personal evaluations regarding the importance of religious education.